Medical TA4G pure titanium wire bar and preparation method thereof
By limiting the oxygen content and adopting multiple vacuum consumable smelting processes, low-oxygen and high-performance TA4G pure titanium wire rods are prepared, which solves the biosafety hazards and insufficient strength of titanium alloy materials during long-term implantation, and achieves high strength and good ductility. It is suitable for high-strength medical implants.
Patent Information
- Application Number
- CN202411936706.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-11
AI Technical Summary
The biosafety hazards that existing titanium alloy materials may bring during long-term implantation, especially the precipitation of vanadium and aluminum elements in Ti-6Al-4V alloys in the human body will affect the biocompatibility of cells and may cause health hazards. At the same time, pure titanium materials have low strength and are difficult to meet the requirements of certain high-strength applications.
By limiting the oxygen content, TA4G pure titanium wire rods with low oxygen and high performance are prepared by using multiple vacuum consumable smelting, billet forging, multi-directional forging water quenching, multi-pass small deformation hot rolling, cold rolling and annealing.
The obtained TA4G pure titanium wire rod has high tensile strength (880MPa~1050MPa) and yield strength (700MPa~900MPa), and has good ductility and toughness, reducing the risk of brittle fracture, and is suitable for high-strength medical implants.
Smart Images

Figure BDA0005211677500000161 
Figure BDA0005211677500000171
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of titanium alloys, and in particular relates to a medical TA4G pure titanium wire rod and a preparation method thereof. Background Art
[0002] As an excellent biomedical material, titanium alloy is widely used in human implants due to its excellent biocompatibility, light weight, corrosion resistance and non-toxicity. Especially in the fields of dentistry, orthopedics, cardiovascular and other fields, the application of titanium alloy is becoming more and more popular. As one of the most commonly used titanium alloys, Ti-6Al-4V alloy has achieved certain application results in medical devices and implants. For example, Ti-6Al-4V alloy is used to manufacture implants such as orthodontic brackets, joint replacements, and fracture fixators, and has achieved good clinical results. However, although the application of Ti-6Al-4V alloy in the medical field has made significant progress, research reports in recent years have revealed the potential biosafety risks of this alloy during long-term implantation. The precipitation of vanadium (V) and aluminum (Al) elements in Ti-6Al-4V alloy in the human body will cause trace amounts of vanadium and aluminum ions to enter the human circulation, thereby affecting the biocompatibility of cells, especially the nervous system and acid-base balance, which may interfere and even cause long-term health hazards. Therefore, although Ti-6Al-4V alloy has high mechanical properties, its potential toxicity during long-term use limits its application in long-term implants.
[0003] Compared with Ti-6Al-4V alloy, pure titanium has superior biocompatibility and non-toxicity as a medical implant material. Titanium has very high chemical stability, which can effectively avoid toxic reactions, and has excellent affinity for human tissue, reducing the risk of foreign body rejection. The corrosion resistance of pure titanium is also far superior to many other metal materials, especially in the complex environment of the human body, and can maintain stability and reliability for a long time. Therefore, in recent years, pure titanium has become an ideal medical implant material widely recognized by the medical community and is widely used in various medical fields such as artificial joints, bone screws, and dental implants. However, a major disadvantage of pure titanium is its relatively low strength, especially compared with other high-strength alloy materials, the mechanical properties of pure titanium often cannot meet the requirements of certain special implants. For implants that need to withstand large mechanical loads, the low strength of pure titanium may cause the implant to deform or rupture, limiting its further application in some high-strength application scenarios.
[0004] In order to solve the problem of low strength of pure titanium materials, relevant studies have proposed a technology to increase the tensile strength of pure titanium by increasing the oxygen content. Commercially available medical pure titanium rods usually use an oxygenation process to improve their mechanical properties. In this process, when the oxygen impurity content increases to 0.35wt.%, the tensile strength of the alloy can reach 700MPa, and the yield strength can reach 610MPa, thus meeting the needs of many high-performance medical implants. However, although the oxygenation process effectively improves the mechanical properties of the material, it also brings new problems. In the process of increasing the oxygen content, the crystal structure of the titanium alloy will undergo certain changes, resulting in crystal defects inside the material, which in turn affects its toughness and ductility, and increases the risk of brittle fracture of the implant. This may bring greater safety hazards to implants that need to withstand biomechanical loads for a long time, especially medical devices that bear large forces or withstand repeated stress. Therefore, although the oxygenation process improves the strength of titanium alloys, it fails to solve the brittleness problem of pure titanium in high-performance applications, which further limits its wide application in some medical fields. In summary, it is still necessary to develop a low-oxygen, high-performance titanium alloy material. Summary of the invention
[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the present invention provides a method for preparing a medical TA4G pure titanium wire rod, by limiting the oxygen content, through multiple vacuum consumable smelting, blank forging, multi-directional forging water quenching, multiple passes of small deformation hot rolling, cold rolling and annealing processes, finally obtaining a medical low-oxygen high-performance TA4G pure titanium wire rod.
[0006] The invention also provides a medical TA4G pure titanium wire rod.
[0007] The first aspect of the present invention provides a method for preparing a medical TA4G pure titanium wire rod, comprising the following steps:
[0008] S1: performing vacuum consumable melting on the alloy raw materials to obtain the first alloy ingot, and then forging the ingot;
[0009] S2: performing multi-directional forging and water quenching treatment on the blank obtained in step S1;
[0010] S3: performing precision radial forging on the blank obtained in step S2;
[0011] S4: The blank obtained in step S3 is subjected to multiple passes of small deformation hot rolling, and then cold rolling, and annealing is performed to obtain the medical TA4G pure titanium wire rod.
[0012] One of the technical solutions of the present invention regarding the medical TA4G pure titanium wire rod has at least the following beneficial effects:
[0013] In view of the deficiencies in the prior art, the present invention limits the oxygen content, and finally obtains a medical low-oxygen and high-performance TA4G pure titanium wire rod through multiple vacuum consumable smelting, blank forging, multi-directional forging water quenching, multiple passes of small deformation hot rolling, cold rolling and annealing processes.
[0014] The preparation method of the medical TA4G pure titanium wire rod of the present invention controls the oxygen mass content below 0.25% during the smelting of the ingot, thereby obtaining a low-oxygen and high-cleanliness ingot, reducing the internal defects of the crystal caused by trace impurity elements from the source, and avoiding the failure problem of the terminal product of the medical device.
[0015] The preparation method of the medical TA4G pure titanium wire rod adopts multi-directional forging and water quenching treatment, and multiple passes of small deformation rolling to fully break the grains in the ingot, thereby obtaining a fine grain structure.
[0016] The preparation method of the medical TA4G pure titanium wire rod of the present invention can prepare TA4G pure titanium wire rod with high cleanliness, low oxygen content, high strength and plasticity and good matching, the tensile strength can reach 880MPa-1050MPa, the yield strength is 700MPa-900MPa, and the elongation after fracture is greater than 20%.
[0017] In step S2, multi-directional forging and water quenching treatment are adopted. During the multi-directional forging process, dislocations are entangled and rearranged with each other, evolving into small-angle grain boundaries. When the deformation continues to increase, the energy between the grains also increases. During the process, the small-angle grain boundaries continuously absorb dislocations and evolve into large-angle grain boundaries to obtain equiaxed fine grains. Rapid water quenching treatment can prevent the ingot structure from continuing to grow grains and annihilate dislocations during the cooling process, thereby better retaining the fine grains formed by the dynamic recrystallization process and the dislocations accumulated by deformation.
[0018] In step S4, multiple passes of rolling with small deformation amounts are adopted, which makes it easier to make the deformation degree greater than the critical deformation degree, thereby achieving the effect of breaking the grain boundaries and refining the grains, thereby improving the strength of the material.
[0019] According to some embodiments of the present invention, the vacuum consumable melting is performed multiple times.
[0020] According to some embodiments of the present invention, the vacuum consumable melting is performed ≥ 3 times.
[0021] According to some embodiments of the present invention, when the number of vacuum consumable melting is 4 times, the arc voltage of the first melting of the vacuum consumable melting is 23-33V.
[0022] According to some embodiments of the present invention, when the number of vacuum consumable melting is 4 times, the first melting current of the vacuum consumable melting is 3000-5500A.
[0023] According to some embodiments of the present invention, when the number of vacuum consumable melting is 4 times, the arc voltage of the second melting of the vacuum consumable melting is 23-34V.
[0024] According to some embodiments of the present invention, when the number of vacuum consumable melting is 4 times, the arc current of the second melting of the vacuum consumable melting is 4000-7000A.
[0025] According to some embodiments of the present invention, when the number of vacuum consumable melting is 4 times, the arc voltage of the third melting of the vacuum consumable melting is voltage: 23-35V.
[0026] According to some embodiments of the present invention, when the number of vacuum consumable melting is 4 times, the third melting current of the vacuum consumable melting is 6000-10000A.
[0027] According to some embodiments of the present invention, when the number of vacuum consumable melting is 4 times, the arc voltage of the fourth melting of the vacuum consumable melting is 23-36V.
[0028] According to some embodiments of the present invention, when the number of vacuum consumable melting is 4 times, the fourth melting current of the vacuum consumable melting is 8000-12000A.
[0029] According to some embodiments of the present invention, the chemical composition of the first alloy ingot is, by mass percentage:
[0030] C:≤0.08%,
[0031] O:≤0.25%,
[0032] N:≤0.05%,
[0033] H:≤0.008%,
[0034] Fe:≤0.50%,
[0035] The remainder is Ti.
[0036] According to some embodiments of the present invention, the method of blank forging includes: peeling and removing the riser of the first alloy ingot to obtain a second ingot, heating the second ingot, and then forging it by upsetting to obtain a third ingot, and grinding and cutting the third ingot to obtain a first blank.
[0037] According to some embodiments of the present invention, the second ingot is heated at a temperature of 850-950°C.
[0038] According to some embodiments of the present invention, the second ingot is heated for a holding time of 90-270 min.
[0039] According to some embodiments of the present invention, the deformation amount of forging processing by upsetting processing is greater than 70%, so as to obtain a third ingot.
[0040] According to some embodiments of the present invention, the diameter of the first blank is 170-220 mm.
[0041] According to some embodiments of the present invention, the multi-directional forging method includes: forging the ingot obtained in step S1 in three mutually perpendicular directions X, Y, and Z for a total of three passes. Before each forging pass, the billet is first heated to 700-850°C and kept warm for 60-120 minutes. The forging deformation is 45-55%. At this time, the forging is stopped and quickly water quenched, and then the next forging is performed until the three directions are forged to obtain a second billet. The diameter of the second billet is 120-160 mm.
[0042] According to some embodiments of the present invention, the method of precision radial forging includes: heating the billet obtained in step S2 at a heating temperature of 700-800°C, keeping it warm for 30-90 minutes, and then performing precision radial forging with a deformation of 75-85% to obtain a third billet, the diameter of the third billet being 55-60 mm.
[0043] According to some embodiments of the present invention, the method of multi-pass small deformation hot rolling includes: heating the billet obtained in step S3, the heating temperature is 700-800°C, and the heat preservation is 30-120min, the deformation of each pass is less than 15%, and the total deformation is greater than 85%, to obtain a hot-rolled rod with a diameter of 14-22mm.
[0044] In the cold rolling of step S4, the hot-rolled rod is firstly stripped by a centerless lathe, the stripping depth is 0.3-1 mm, and then the rod is cold-rolled by roller mill, the deformation amount of each pass is less than 10%, and the total deformation amount is 40-60%, and then stress relief annealing is performed, and the cycle is repeated for multiple times to obtain a wire rod, and the wire rod diameter is 5-12 mm;
[0045] After cold rolling and before annealing, the wire rod is straightened, and the straightness after straightening is ≤1mm / m. The straightened rod blank is annealed at a temperature of 550-750℃, kept warm for 30-120min, and air-cooled.
[0046] According to some embodiments of the present invention, the preparation method of medical TA4G pure titanium wire rod may be:
[0047] Step 1: preparing a titanium-zirconium alloy ingot by vacuum consumable smelting;
[0048] Step 2: Forging the blank;
[0049] Step 3: multi-directional forging and water quenching;
[0050] Step 4: Precision radial forging;
[0051] Step 5: hot rolling with multiple passes and small deformation;
[0052] Step six, cold rolling;
[0053] Step seven: annealing to obtain low-oxygen high-performance TA4G pure titanium wire rod.
[0054] In step one:
[0055] Weigh raw materials according to the ratio, the raw materials include grade 1, grade 0 or grade 0A sponge titanium and iron powder, mix the raw materials and press them into electrode blocks and weld them, perform vacuum consumable smelting on the electrode blocks for no less than 3 times to obtain a first ingot, the chemical composition (mass percentage) of the first ingot is: C: ≤0.08%, O: ≤0.25%, N: ≤0.05%, H: ≤0.008%, Fe: ≤0.50%, and the balance is Ti.
[0056] In step 2:
[0057] The first ingot is peeled and the riser is removed to obtain a second ingot; the second ingot is heated to a temperature of 850-950°C and a holding time of 90-270 minutes, and then forged by a hydraulic fast forging machine in an upsetting and drawing form with a deformation amount of more than 70% to obtain a third ingot; the third ingot is ground and cut to obtain a first billet, and the size of the first billet is 170-220 mm.
[0058] In step three:
[0059] The billet is forged in three mutually perpendicular directions, X, Y, and Z, for a total of three passes. Before each forging pass, the billet is heated to 700-850°C and kept warm for 60-120 minutes. The forging deformation is 45-55%. At this time, the forging is stopped and quickly water quenched, and then the next forging is carried out until the three directions are forged to obtain the second billet. The size of the second billet is Φ120-160mm.
[0060] In step 4:
[0061] The second blank is heated to 700-800°C for 30-90 minutes, and then precision radial forging is performed with a deformation amount of 75-85% to obtain a third blank with a size of Φ55-60mm.
[0062] In step five:
[0063] The third billet is heated to 700-800°C and kept warm for 30-120 minutes. The deformation amount of each pass is less than 15%, and the total deformation amount is greater than 85%, so as to obtain a hot-rolled rod with a size of Φ14-22mm.
[0064] In step six:
[0065] First, the hot-rolled rod is stripped by a centerless lathe with a stripping depth of 0.3-1mm, and then the rod is cold-rolled by roller mill, with each pass deformation less than 10% and a total deformation of 40-60%. Subsequently, stress relief annealing is performed, and the process is repeated many times to obtain a wire rod with a size of Φ5-12mm.
[0066] In step seven:
[0067] The wire rod is straightened, and the straightness after straightening is ≤1mm / m. The straightened rod blank is annealed at a temperature of 550-750℃, kept warm for 30-120min, and air-cooled.
[0068] The mechanical properties of medical low-oxygen high-performance TA4G pure titanium wire rod are: tensile strength 880MPa~1050MPa, yield strength 700MPa~900MPa, and elongation greater than 20%.
[0069] The second aspect of the present invention provides a medical TA4G pure titanium wire rod, which is prepared by the preparation method of the first aspect of the present invention.
[0070] One of the technical solutions of the present invention regarding the medical TA4G pure titanium wire rod has at least the following beneficial effects:
[0071] 1. Low oxygen and high cleanliness: By controlling the oxygen mass content below 0.25% and using a vacuum consumable melting process, low-oxygen, high-cleanliness alloy ingots can be obtained. The plastic deformation of titanium alloys is achieved through dislocation slip. The increase in oxygen atoms hinders slip, and the layered structure weakens the plasticity, easily produces holes, and provides channels for the diffusion of O atoms, which greatly accelerates the diffusion reaction, precipitates TiO phase at the grain boundary, and causes O segregation, resulting in reduced grain boundary strength and inducing alloy embrittlement. This is especially important for medical devices, because alloy embrittlement may lead to fatigue fracture or early failure of implants. Therefore, this preparation method can improve the reliability of the final product, especially in implants that are used for a long time, and can reduce the potential risk of failure.
[0072] 2. Fine grain structure: The combination of multi-directional forging and water quenching can effectively break up the large grains in the ingot, making the grains of the alloy small and uniform. The fine grains not only improve the mechanical properties of the material (such as tensile strength and yield strength), but also improve its ductility and toughness. Fine grains can effectively improve the strength of the material while maintaining good plasticity and reducing the risk of brittle fracture, especially during the use of medical devices, under dynamic loads, the fine grain structure can better cope with mechanical stress.
[0073] 3. High strength and good plasticity: The multi-pass small deformation rolling process is used to refine the grains and enhance the strength of the material. The final TA4G pure titanium wire rod has high tensile strength (880MPa~1050MPa), yield strength (700MPa~900MPa), and good ductility (elongation after fracture is greater than 20%). The high strength and good plasticity of this material enable it to maintain stability and reliability for a long time in a complex biomechanical environment, and is suitable for the manufacture of high-strength, high-load medical implants, such as orthopedic implants, dental implants, etc.
[0074] 4. Fatigue resistance and durability: By refining the grains and improving the strength, the medical TA4G pure titanium wire rod also performs well in fatigue resistance. The durability and long-term biocompatibility of the material have been enhanced, and it can better withstand repeated loading or long-term dynamic loads. This makes its application in high-strength medical devices safer, especially in the fields of long-term implants such as joint replacements, bone nails, fracture fixators, etc., which can effectively prevent early failure of implants.
[0075] 5. Excellent comprehensive performance: This preparation method optimizes the process flow to make TA4G pure titanium wire rod outstanding in comprehensive performance. In addition to strength and plasticity, the material also has good matching and biocompatibility. Its performance can meet the high requirements of various medical implants for mechanical properties and biocompatibility.
[0076] The medical TA4G pure titanium wire rod of the present invention has effectively improved mechanical properties, reduced oxygen content, refined grains, and increased strength and plasticity, has long-term stability and safety in medical implants, and has broad application prospects in high-load medical devices and long-term implants.
[0077] According to some embodiments of the present invention, the diameter of the medical TA4G pure titanium wire rod is 5-12 mm.
[0078] According to some embodiments of the present invention, the tensile strength of the medical TA4G pure titanium wire rod is 880 MPa to 1050 MPa.
[0079] According to some embodiments of the present invention, the yield strength of the medical TA4G pure titanium wire rod is 700 MPa to 900 MPa.
[0080] According to some embodiments of the present invention, the elongation of the medical TA4G pure titanium wire rod is greater than 20%. DETAILED DESCRIPTION
[0081] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0082] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0083] Unless otherwise specified, "room temperature" in the present invention means 25°C±5°C.
[0084] Unless otherwise specified, "about" in the present invention means that the allowable error is within ±2%.
[0085] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0086] It should be noted that GB / T3620.1-2016 stipulates: C: ≤0.08%, O: ≤0.40%, N: ≤0.05%, H: ≤0.008%, Fe: ≤0.50%, and the balance is Ti. In the present invention, C: ≤0.08%, O: ≤0.25%, N: ≤0.05%, H: ≤0.008%, Fe: ≤0.50%, and the balance is Ti.
[0087] Example 1
[0088] A method for preparing medical TA4G pure titanium wire rod, specifically comprising:
[0089] Step 1, use 0 grade titanium sponge and iron powder according to the composition of pure titanium alloy, press the electrode and weld it, use vacuum consumable to melt four times, the arc voltage of the first melting is 23-33V, the current is 3000-5500A; the arc voltage of the second melting is 23-34V, the current is 4000-7000A; the arc voltage of the third melting is 23-35V, the current is 6000-10000A; the arc voltage of the fourth melting is 23-36V, the current is 8000-12000A; obtain Φ450mm pure titanium ingot, the mass percentage of which includes: C: 0.049%, O: 0.207%, N: 0.0048%, H: 0.0012%, Fe: 0.35%, and the balance is Ti;
[0090] It should be noted that during the vacuum consumable melting process, the actual current and voltage will fluctuate within a limited range, so they are range values rather than fixed point values.
[0091] Step 2: peel the ingot, remove the riser and heat it at 900°C. After 180 minutes of holding time, use a hydraulic fast forging machine to forge it. Perform three upsetting and drawing operations with a deformation of 85%. Then, grind and cut it to obtain the first blank. The size of the first blank is 170 mm.
[0092] Step 3, the first blank is forged and quenched in three mutually perpendicular directions X, Y, and Z for a total of three passes. First, the blank is kept at 850° C. for 120 minutes, forged in the X direction, the forging deformation is 50%, and immediately water quenched. Then, the blank is kept at 850° C. for 120 minutes, the direction is turned, and forged in the Y direction, the forging deformation is 50%, and immediately water quenched. Finally, the blank is kept at 850° C. for 120 minutes, the direction is turned, and forged in the Z direction, the forging deformation is 50%, and immediately water quenched to obtain a second blank. The size of the second blank is Φ120 mm.
[0093] Step 4: After keeping the second batch of materials at 800°C for 120 minutes, forging them with a precision radial forging machine, with the deformation controlled at 79%, to obtain a Φ55mm third billet;
[0094] Step 5: After the second batch of materials is kept at 800°C for 60 minutes, they are hot rolled using a horizontal reciprocating rolling mill, with the deformation of each pass controlled below 13% and the total deformation being 94%, to obtain Φ14mm hot-rolled bars;
[0095] Step 6: Use a centerless lathe to peel the hot-rolled bar, the peeling depth is 0.5mm, the hot-rolled bar size is Φ13mm, and then the hot-rolled bar is roller-milled and cold-rolled, the single-pass deformation is 10%, and after the deformation reaches 40%-45%, intermediate annealing is performed, the annealing system is 650℃, 60min, and after multiple cycles, a Φ6mm bar is obtained;
[0096] Step seven, use a multi-roll straightening machine to straighten the rod, the straightness after straightening is 0.2mm / m, then anneal at 600°C, keep warm for 120min, air cool, and obtain TA4G pure titanium wire rod finished product.
[0097] Example 2
[0098] A method for preparing medical TA4G pure titanium wire rod, specifically comprising:
[0099] Step 1, use 0 grade titanium sponge and iron powder according to the composition of pure titanium alloy, press the electrode and weld it, use vacuum consumable to melt four times, the arc voltage of the first melting is 23-33V, the current is 3000-5500A; the arc voltage of the second melting is 23-34V, the current is 4000-7000A; the arc voltage of the third melting is 23-35V, the current is 6000-10000A; the arc voltage of the fourth melting is 23-36V, the current is 8000-12000A; obtain Φ450mm pure titanium ingot, the mass percentage of which includes: C: 0.049%, O: 0.207%, N: 0.0048%, H: 0.0012%, Fe: 0.35%, and the balance is Ti;
[0100] Step 2: peel the ingot, remove the riser and heat it at 900°C. After 180 minutes of holding time, use a hydraulic fast forging machine to forge it. Perform three upsetting and drawing operations with a deformation of 85%. Then, grind and cut it to obtain the first blank. The size of the first blank is 170 mm.
[0101] Step 3, the first blank is forged and quenched in three mutually perpendicular directions X, Y, and Z for a total of three passes. First, the blank is kept at 850° C. for 120 minutes, forged in the X direction, the forging deformation is 50%, and immediately water quenched. Then, the blank is kept at 850° C. for 120 minutes, the direction is turned, and forged in the Y direction, the forging deformation is 50%, and immediately water quenched. Finally, the blank is kept at 850° C. for 120 minutes, the direction is turned, and forged in the Z direction, the forging deformation is 50%, and immediately water quenched to obtain a second blank. The size of the second blank is Φ120 mm.
[0102] Step 4: After keeping the second batch of materials at 800°C for 120 minutes, forging them with a precision radial forging machine, with the deformation controlled at 75%, to obtain a Φ60 mm third billet;
[0103] Step 5: After the second batch of materials is kept at 800°C for 60 minutes, hot rolling is performed using a horizontal reciprocating rolling mill, with the deformation of each pass controlled below 15% and the total deformation being 92%, to obtain a Φ16.2 mm hot-rolled bar;
[0104] Step 6: Use a centerless lathe to peel the hot-rolled bar, the peeling depth is 0.5mm, the hot-rolled bar size is Φ15.2mm, and then the hot-rolled bar is roller-milled and cold-rolled, the single-pass deformation is 12%, and after the deformation reaches 40%-45%, intermediate annealing is performed, the annealing system is 650℃, 60min, and after multiple cycles, a Φ6.1mm bar is obtained;
[0105] Step seven, use a multi-roll straightening machine to straighten the rod, the straightness after straightening is 0.1mm / m, then annealing is performed at a temperature of 610°C, the temperature is kept for 120 minutes, and air cooling is performed to obtain a TA4G pure titanium wire rod finished product.
[0106] Example 3
[0107] A method for preparing medical TA4G pure titanium wire rod, specifically comprising:
[0108] Step 1, use 0 grade titanium sponge and iron powder according to the composition of pure titanium alloy, press the electrode and weld it, use vacuum consumable to melt four times, the arc voltage of the first melting is 23-33V, the current is 3000-5500A; the arc voltage of the second melting is 23-34V, the current is 4000-7000A; the arc voltage of the third melting is 23-35V, the current is 6000-10000A; the arc voltage of the fourth melting is 23-36V, the current is 8000-12000A; obtain Φ450mm pure titanium ingot, the mass percentage of which includes: C: 0.049%, O: 0.207%, N: 0.0048%, H: 0.0012%, Fe: 0.35%, and the balance is Ti;
[0109] Step 2: peel the ingot, remove the riser and heat it at 900°C. After 180 minutes of holding time, use a hydraulic fast forging machine to forge it. Perform three upsetting and drawing operations with a deformation of 85%. Then, grind and cut it to obtain the first blank. The size of the first blank is 170 mm.
[0110] Step 3, the first blank is forged and quenched in three mutually perpendicular directions X, Y, and Z for a total of three passes. First, the blank is kept at 850° C. for 120 minutes, forged in the X direction, the forging deformation is 50%, and immediately water quenched. Then, the blank is kept at 850° C. for 120 minutes, the direction is turned, and forged in the Y direction, the forging deformation is 50%, and immediately water quenched. Finally, the blank is kept at 850° C. for 120 minutes, the direction is turned, and forged in the Z direction, the forging deformation is 50%, and immediately water quenched to obtain a second blank. The size of the second blank is Φ120 mm.
[0111] Step 4: After keeping the second batch of materials at 800°C for 120 minutes, forging them with a precision radial forging machine, with the deformation controlled at 75%, to obtain a Φ60 mm third billet;
[0112] Step 5: After the second batch of materials is kept at 800°C for 60 minutes, hot rolling is performed using a horizontal reciprocating rolling mill, with the deformation of each pass controlled below 13% and the total deformation being 95%, to obtain a Φ14 mm hot-rolled bar;
[0113] Step 6: Use a centerless lathe to peel the hot-rolled bar, the peeling depth is 0.5mm, the hot-rolled bar size is Φ13mm, and then the hot-rolled bar is roller-milled and cold-rolled, the single-pass deformation is 10%, and after the deformation reaches 40%-45%, intermediate annealing is performed, the annealing system is 650℃, 60min, and after multiple cycles, a Φ5.5mm bar is obtained;
[0114] Step seven, use a multi-roll straightening machine to straighten the rod, the straightness after straightening is 0.1mm / m, and then annealing is performed at a temperature of 600°C, the temperature is kept for 120 minutes, and air-cooling is performed to obtain a finished TA4G pure titanium wire rod.
[0115] Example 4
[0116] A method for preparing medical TA4G pure titanium wire rod, specifically comprising:
[0117] Step 1, use 0 grade titanium sponge and iron powder according to the composition of pure titanium alloy, press the electrode and weld it, use vacuum consumable to melt four times, the arc voltage of the first melting is 23-33V, the current is 3000-5500A; the arc voltage of the second melting is 23-34V, the current is 4000-7000A; the arc voltage of the third melting is 23-35V, the current is 6000-10000A; the arc voltage of the fourth melting is 23-36V, the current is 8000-12000A; obtain Φ370mm pure titanium ingot, the mass percentage of which includes: C: 0.016%, O: 0.192%, N: 0.0050%, H: 0.0014%, Fe: 0.226%, and the balance is Ti;
[0118] Step 2: peel the ingot, remove the riser and heat it at 900°C. After 180 minutes of holding time, use a hydraulic fast forging machine to forge it. After three upsetting and drawing processes, the deformation is 83%, and then grind and cut it. The first billet is obtained, and the size of the first billet is 150mm;
[0119] Step 3, the first blank is forged and quenched in three mutually perpendicular directions X, Y, and Z for a total of three passes. First, the blank is kept at 820° C. for 150 minutes, forged in the X direction, the forging deformation is 50%, and immediately water quenched. Then, the blank is kept at 820° C. for 150 minutes, the direction is turned, and forged in the Y direction, the forging deformation is 50%, and immediately water quenched. Finally, the blank is kept at 820° C. for 150 minutes, the direction is turned, and forged in the Z direction, the forging deformation is 50%, and immediately water quenched to obtain a second blank. The size of the second blank is Φ106 mm.
[0120] Step 4: After keeping the second batch of materials at 800°C for 150 minutes, forging them with a precision radial forging machine, with the deformation controlled at 65%, to obtain a Φ60 mm third billet;
[0121] Step 5: After the second batch of materials is kept at 800°C for 90 minutes, hot rolling is performed using a horizontal reciprocating rolling mill, with the deformation amount of each pass controlled below 15% and the total deformation amount being 95%, to obtain a Φ12.8 mm hot-rolled bar;
[0122] Step 6: Use a centerless lathe to peel the hot-rolled bar, the peeling depth is 0.4mm, the hot-rolled bar size is Φ12mm, and then the hot-rolled bar is roller-milled and cold-rolled, the single-pass deformation is 12%, and after the deformation reaches 40%-45%, intermediate annealing is performed, the annealing system is 650℃, 90min, and after multiple cycles, a Φ4.8mm bar is obtained;
[0123] Step seven, use a multi-roll straightening machine to straighten the rod, the straightness after straightening is 0.2mm / m, then annealing is performed at a temperature of 580°C, the temperature is kept for 120 minutes, and air cooling is performed to obtain a TA4G pure titanium wire rod finished product.
[0124] Comparative Example 1
[0125] A method for preparing a medical TA4G pure titanium wire rod, in which multi-directional forging and water quenching are not performed in this comparative example, specifically:
[0126] Step 1, use 0 grade titanium sponge and iron powder according to the composition of pure titanium alloy, press the electrode and weld it, use vacuum consumable to melt four times, the arc voltage of the first melting is 23-33V, the current is 3000-5500A; the arc voltage of the second melting is 23-34V, the current is 4000-7000A; the arc voltage of the third melting is 23-35V, the current is 6000-10000A; the arc voltage of the fourth melting is 23-36V, the current is 8000-12000A; obtain Φ450mm pure titanium ingot, the mass percentage of which includes: C: 0.049%, O: 0.207%, N: 0.0048%, H: 0.0012%, Fe: 0.35%, and the balance is Ti;
[0127] Step 2: peel the ingot, remove the riser and heat it at 900°C. After 180 minutes of holding time, use a hydraulic fast forging machine to forge it. Perform three upsetting and drawing operations with a deformation of 85%. Then, grind and cut it to obtain the first blank. The size of the first blank is 170 mm.
[0128] Step 3: After the first batch of materials is kept at 900°C for 180 minutes, it is forged using a precision radial forging machine, with the deformation amount controlled at 50%, to obtain a Φ120 mm third billet;
[0129] Step 4: After keeping the second batch of materials at 800°C for 120 minutes, forging them with a precision radial forging machine, with the deformation controlled at 79%, to obtain a Φ55mm third billet;
[0130] Step 5: After the second batch of materials is kept at 800°C for 60 minutes, they are hot rolled using a horizontal reciprocating rolling mill, with the deformation of each pass controlled below 13% and the total deformation being 94%, to obtain Φ14mm hot-rolled bars;
[0131] Step 6: Use a centerless lathe to peel the hot-rolled bar, the peeling depth is 0.5mm, the hot-rolled bar size is Φ13mm, and then the hot-rolled bar is roller-milled and cold-rolled, the single-pass deformation is 10%, and after the deformation reaches 40%-45%, intermediate annealing is performed, the annealing system is 650℃, 60min, and after multiple cycles, a Φ6mm bar is obtained;
[0132] Step seven, use a multi-roll straightening machine to straighten the rod, the straightness after straightening is 0.2mm / m, then anneal at 600°C, keep warm for 120min, air cool, and obtain TA4G pure titanium wire rod finished product.
[0133] Comparative Example 2
[0134] A method for preparing a medical TA4G pure titanium wire rod, in which no water quenching is performed in this comparative example, specifically:
[0135] Step 1, use 0 grade titanium sponge and iron powder according to the composition of pure titanium alloy, press the electrode and weld it, use vacuum consumable to melt four times, the arc voltage of the first melting is 23-33V, the current is 3000-5500A; the arc voltage of the second melting is 23-34V, the current is 4000-7000A; the arc voltage of the third melting is 23-35V, the current is 6000-10000A; the arc voltage of the fourth melting is 23-36V, the current is 8000-12000A; obtain Φ450mm pure titanium ingot, the mass percentage of which includes: C: 0.049%, O: 0.207%, N: 0.0048%, H: 0.0012%, Fe: 0.35%, and the balance is Ti;
[0136] Step 2: peel the ingot, remove the riser and heat it at 900°C. After 180 minutes of holding time, use a hydraulic fast forging machine to forge it. Perform three upsetting and drawing operations with a deformation of 85%. Then, grind and cut it to obtain the first blank. The size of the first blank is 170 mm.
[0137] Step 3, the first blank is forged and quenched in three mutually perpendicular directions X, Y, and Z for a total of three passes. First, the blank is kept at 850° C. for 120 minutes, forged in the X direction, the forging deformation is 50%, and air-cooled. Then, the blank is kept at 850° C. for 120 minutes, the direction is turned, and forged in the Y direction, the forging deformation is 50%, and air-cooled. Finally, the blank is kept at 850° C. for 120 minutes, the direction is turned, and forged in the Z direction, the forging deformation is 50%, and air-cooled to obtain a second blank. The size of the second blank is Φ120 mm.
[0138] Step 4: After keeping the second batch of materials at 800°C for 120 minutes, forging them with a precision radial forging machine, with the deformation controlled at 79%, to obtain a Φ55mm third billet;
[0139] Step 5: After the second batch of materials is kept at 800°C for 60 minutes, they are hot rolled using a horizontal reciprocating rolling mill, with the deformation of each pass controlled below 13% and the total deformation being 94%, to obtain Φ14mm hot-rolled bars;
[0140] Step 6: Use a centerless lathe to peel the hot-rolled bar, the peeling depth is 0.5mm, the hot-rolled bar size is Φ13mm, and then the hot-rolled bar is roller-milled and cold-rolled, the single-pass deformation is 10%, and after the deformation reaches 40%-45%, intermediate annealing is performed, the annealing system is 650℃, 60min, and after multiple cycles, a Φ6mm bar is obtained;
[0141] Step seven, use a multi-roll straightening machine to straighten the rod, the straightness after straightening is 0.2mm / m, then anneal at 600°C, keep warm for 120min, air cool, and obtain TA4G pure titanium wire rod finished product.
[0142] Comparative Example 3
[0143] A preparation method of a medical TA4G pure titanium wire rod, in which a small number of passes and a large deformation amount of rolling are used in this comparative example, specifically:
[0144] Step 1, use 0 grade titanium sponge and iron powder according to the composition of pure titanium alloy, press the electrode and weld it, use vacuum consumable to melt four times, the arc voltage of the first melting is 23-33V, the current is 3000-5500A; the arc voltage of the second melting is 23-34V, the current is 4000-7000A; the arc voltage of the third melting is 23-35V, the current is 6000-10000A; the arc voltage of the fourth melting is 23-36V, the current is 8000-12000A; obtain Φ450mm pure titanium ingot, the mass percentage of which includes: C: 0.049%, O: 0.207%, N: 0.0048%, H: 0.0012%, Fe: 0.35%, and the balance is Ti;
[0145] Step 2: peel the ingot, remove the riser and heat it at 900°C. After 180 minutes of holding time, use a hydraulic fast forging machine to forge it. Perform three upsetting and drawing operations with a deformation of 85%. Then, grind and cut it to obtain the first blank. The size of the first blank is 170 mm.
[0146] Step 3, the first blank is forged and quenched in three mutually perpendicular directions X, Y, and Z for a total of three passes. First, the blank is kept at 850° C. for 120 minutes, forged in the X direction, the forging deformation is 50%, and immediately water quenched. Then, the blank is kept at 850° C. for 120 minutes, the direction is turned, and forged in the Y direction, the forging deformation is 50%, and immediately water quenched. Finally, the blank is kept at 850° C. for 120 minutes, the direction is turned, and forged in the Z direction, the forging deformation is 50%, and immediately water quenched to obtain a second blank. The size of the second blank is Φ120 mm.
[0147] Step 4: After keeping the second batch of materials at 800°C for 120 minutes, forging them with a precision radial forging machine, with the deformation controlled at 79%, to obtain a Φ55mm third billet;
[0148] Step 5: After the second batch of materials is kept at 800°C for 60 minutes, hot rolling is performed using a horizontal reciprocating rolling mill, with the deformation amount of each pass controlled below 25% and the total deformation amount being 94%, to obtain a Φ14 mm hot-rolled bar;
[0149] Step 6: Use a centerless lathe to peel the hot-rolled bar, the peeling depth is 0.5mm, the hot-rolled bar size is Φ13mm, and then the hot-rolled bar is roller-milled and cold-rolled, the single-pass deformation is 10%, and after the deformation reaches 40%-45%, intermediate annealing is performed, the annealing system is 650℃, 60min, and after multiple cycles, a Φ6mm bar is obtained;
[0150] Step seven, use a multi-roll straightening machine to straighten the rod, the straightness after straightening is 0.2mm / m, then anneal at 600°C, keep warm for 120min, air cool, and obtain TA4G pure titanium wire rod finished product.
[0151] According to GB / T 228.1-2021 "Tensile test of metallic materials Part 1: Room temperature test method", the performance of the TA4G pure titanium wire rod products prepared in the embodiment and comparative example was tested, and the results are shown in Table 1.
[0152] Table 1 shows the performance test results of the TA4G pure titanium wire rod product obtained in the implementation case
[0153]
[0154]
[0155] It can be seen from the data in Table 1 that the mechanical properties of the TA4G pure titanium wire rod obtained in the embodiment are significantly better than those of the control group samples, and meet or exceed the requirements of the GB / T13810-2017 standard. The specific analysis is as follows:
[0156] 1. Tensile strength and yield strength
[0157] The tensile strength and yield strength of the samples in the examples are generally higher than those in the comparative examples. For example, the tensile strength of Example 1 is 915 MPa, while the tensile strength of Comparative Example 1 is 746 MPa, with a difference of up to 169 MPa, indicating that the strength of the materials prepared in the examples is significantly improved.
[0158] In terms of yield strength, the yield strength of the examples is generally above 785 MPa, while the yield strength of the comparative example group is as low as 602 MPa, which is a large difference. This shows that the materials of the examples have a strong advantage in bearing capacity.
[0159] 2. Elongation after fracture and section shrinkage
[0160] Comparative data show that the embodiment is superior to the comparative example in strength, and the elongation after fracture is slightly lower, but the cross-sectional shrinkage rate does not decrease, which means that the overall strength and toughness of the material are better balanced and meet the requirements of high-performance medical materials.
[0161] 3. Comparison with standards
[0162] According to GB / T13810-2017, the minimum requirements for TA4G pure titanium wire rods are tensile strength ≥580MPa, yield strength ≥485MPa, elongation after fracture ≥15%, and cross-sectional shrinkage ≥25%. From the data in the table, the materials in the examples clearly exceed these standard requirements.
[0163] The low oxygen content process (oxygen content controlled below 0.25%) used in the embodiment of the present invention has an important impact on the microstructure of the material. The low oxygen content reduces the defects inside the crystal and improves the overall strength of the alloy. Compared with the control group, the material in the embodiment shows stronger tensile strength and yield strength.
[0164] Furthermore, the embodiment adopts a multi-directional forging and water quenching process, which effectively refines the grains and forms a more uniform grain structure. Fine grains can significantly enhance the strength of the material because fine grains hinder the slip of dislocations and increase the strength of the material.
[0165] In addition, water quenching can quickly lock the grain structure and prevent further grain growth, thereby enhancing the mechanical properties of the material.
[0166] Furthermore, the process of rolling with multiple passes and small deformations further refines the grain size of the material, strengthens the strength of the material and improves the plasticity. This process gradually changes the shape of the material, increases the plasticity of the material, promotes the strengthening of the grain boundaries and the refinement of the grains, and further improves the tensile strength.
[0167] Although the materials in the comparison group showed good plasticity in some aspects (such as higher elongation after fracture), the materials in the examples maintained good plasticity (such as higher section shrinkage) while ensuring high strength through optimized processes. This shows that in the preparation method of the examples, strength and plasticity are well balanced, meeting the comprehensive performance requirements of medical titanium alloy materials.
[0168] By analyzing the data in Table 1, it can be concluded that the TA4G pure titanium wire rod prepared in the embodiment is superior to the control group in terms of tensile strength, yield strength, elongation after fracture and cross-sectional shrinkage, and meets or exceeds the requirements of relevant standards. This is due to the control of low oxygen content, the microstructure of fine grains, the application of multi-directional forging and water quenching treatment. These processes work together to improve the overall performance of the material, especially the balance of strength and plasticity, and meet the needs of high-performance medical implant materials.
[0169] The present invention provides a method for preparing a medical low-oxygen high-performance TA4G pure titanium wire rod. When smelting the ingot, the oxygen mass content is controlled below 0.25% to obtain a low-oxygen and high-cleanliness ingot, thereby reducing the internal defects of the crystal caused by trace impurity elements from the source and avoiding the failure problem of medical device terminal products.
[0170] In the preparation method of the present invention, multi-directional forging and water quenching treatment, as well as multiple passes of small deformation rolling are adopted to fully break up the crystal grains in the ingot, thereby obtaining a structure of fine crystal grains.
[0171] TA4G pure titanium wire rod has high cleanliness, low oxygen content, high strength and plasticity, and good matching. The tensile strength is 880MPa~1050MPa, the yield strength is 700MPa~900MPa, and the elongation after fracture is greater than 20%.
[0172] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A method for preparing medical TA4G pure titanium wire rod, characterized in that: The steps include: S1: performing vacuum consumable melting on the alloy raw materials to obtain the first alloy ingot, and then forging the ingot; S2: performing multi-directional forging and water quenching treatment on the blank obtained in step S1; S3: performing precision radial forging on the blank obtained in step S2; S4: The blank obtained in step S3 is subjected to multiple passes of small deformation hot rolling, and then cold rolling, and annealing is performed to obtain the medical TA4G pure titanium wire rod.
2. The preparation method according to claim 1, characterized in that: The vacuum consumable melting is performed ≥3 times.
3. The preparation method according to claim 2, characterized in that: When the number of vacuum consumable melting is 4 times, the first melting arc voltage of the vacuum consumable melting is 23-33V; and / or, the first melting current of the vacuum consumable melting is 3000-5500A; and / or, the second melting arc voltage of the vacuum consumable melting is 23-34V; and / or, the second melting arc current of the vacuum consumable melting is 4000-7000A; and / or, the third melting arc voltage of the vacuum consumable melting is voltage: 23-35V; and / or, the third melting current of the vacuum consumable melting is 6000-10000A; and / or, the fourth melting arc voltage of the vacuum consumable melting is 23-36V; and / or, the fourth melting current of the vacuum consumable melting is 8000-12000A.
4. The preparation method according to claim 1, characterized in that: The chemical composition of the first alloy ingot is as follows, by mass percentage: C:≤0.08%, O:≤0.25%, N:≤0.05%, H:≤0.008%, Fe:≤0.50%, The remainder is Ti.
5. The preparation method according to claim 1, characterized in that: The method for blank forging comprises: peeling and removing risers from the first alloy ingot to obtain a second ingot, heating the second ingot, and then forging the ingot by upsetting to obtain a third ingot, and grinding and cutting the third ingot to obtain a first blank; and / or, the temperature at which the second ingot is heated is 850-950° C.; and / or, the second ingot is heated for a holding time of 90-270 min; and / or, the deformation amount of forging by upsetting is greater than 70%; and / or, the diameter of the first blank is 170-220 mm.
6. The preparation method according to claim 1, characterized in that: The multi-directional forging method comprises: forging the blank obtained in step S1 in three mutually perpendicular directions X, Y, and Z for a total of three passes, before each forging pass, the blank is first heated to 700-850°C and kept warm for 60-120 minutes, the forging deformation is 45-55%, then the forging is stopped and water quenched quickly, and then the next forging is performed until the three directions are forged to obtain a second blank, and the diameter of the second blank is 120-160 mm.
7. The preparation method according to claim 1, characterized in that: The method for precision radial forging comprises: heating the blank obtained in step S2 at a heating temperature of 700-800°C, keeping the temperature for 30-90 minutes, and then performing precision radial forging with a deformation amount of 75-85% to obtain a third blank with a diameter of 55-60 mm.
8. The preparation method according to claim 1, characterized in that: The method for multi-pass small deformation hot rolling comprises: heating the billet obtained in step S3 at a heating temperature of 700-800°C for 30-120 minutes, with the deformation of each pass being less than 15% and the total deformation being greater than 85%, to obtain a hot-rolled rod with a diameter of 14-22 mm.
9. A medical TA4G pure titanium wire rod, characterized in that: The method is prepared according to any one of claims 1 to 8.
10. The medical TA4G pure titanium wire rod according to claim 9, characterized in that: The diameter of the medical TA4G pure titanium wire rod is 5-12 mm; and / or, the tensile strength of the medical TA4G pure titanium wire rod is 880 MPa-1050 MPa; and / or, the yield strength of the medical TA4G pure titanium wire rod is 700 MPa-900 MPa; and / or, the elongation of the medical TA4G pure titanium wire rod is greater than 20%.
Citation Information
Cited By
Preparation method for improving strength of pure titanium bar
CN120796753A
A method for improving the strength of pure titanium bar
CN120796753B